Data on cerebral palsy in Vietnam will inform clinical practice and policy in low and middle-income countries. Issue 13 (19th June 2022) - Karim, Tasneem; Dossetor, Rachael; Huong Giang, Nguyen Thi; Dung, Trinh Quang; Son, Tran Vinh; Hoa, Nguyen Xuan; Tuyet, Nguyen Hong; Van Anh, Nguyen Thi; Chau, Cao Minh; Bang, Nguyen Van; Badawi, Nadia; Khandaker, Gulam; et al.
Abstract: Purpose: To document known risk factors, clinical severity, associated impairments and rehabilitation status of children presenting with cerebral palsy (CP) to the National Children's Hospital (NCH) in Hanoi, Vietnam. Materials and methods: Active prospective ascertainment of cases of CP presenting between June and November 2017 to the NCH using surveillance modelled on the Paediatric Active Enhanced Disease Surveillance system in Australia. Results: Data were collected on 765 children with CP (mean age: 2 years 7 months (SD 2 y 6 mo). Mean age at diagnosis was 1 year 8 months (SD 1 y 9 mo). Children predominantly had spastic CP (95.2%, n  = 729), most were quadriplegic (69.6%, n  = 532) and 60.3% ( n  = 454) were Gross Motor Functional Classification System level III-V. Of the children 76.2% ( n  = 583) had one/more associated impairments. 36.3% ( n  = 276) had presumed perinatal asphyxia, 26.5% ( n  = 202) were preterm. Physiotherapy (94.3%, n  = 663) was the most common form of intervention used. Only 2.6% ( n  = 12) of the children who would have benefitted from assistive devices had wheelchairs. Conclusion: We established hospital-based surveillance of CP in Hanoi and confirmed a high burden and severity of CP with potentially preventable risk factors. These data will inform clinician training and health policy and identify need for evidence-based care and assistive devices. IMPLICATIONS FOR REHABILITATION: We identified a high number of children with severe forms of cerebral palsy (CP) in Hanoi, Vietnam through hospital-based surveillance. There is an urgent need for clinician training and access to and use of evidence-based interventions including assistive technology. This study will inform local capacity building and health policy for improved diagnosis and care of children with CP in Vietnam and other low and middle-income countries.